Question
upstudy study bank question image url

Calculate the gradient of the tangent to the curve \( y=4 x^{2}-2 x+1 \) at \( (2,13) \). The curve \( y=a x^{2}-\frac{b}{x} \) has gradients 3 and -2 at \( x=1 \) and \( x=\frac{1}{2} \) respectively. Find the values of \( a \) and \( b \). \( \begin{array}{ll}\text { a) } \frac{d y}{d x}=8 x-2\end{array} \)

Ask by Chambers Joseph. in Singapore
Jan 11,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The gradient of the tangent to the curve \( y = 4x^2 - 2x + 1 \) at the point \( (2, 13) \) is **14**. For the curve \( y = ax^2 - \frac{b}{x} \), the values are \( a = 2 \) and \( b = -1 \).

Solution

Let's address each part of your question step by step. ### 1. Gradient of the Tangent to the Curve \( y = 4x^2 - 2x + 1 \) at \( (2, 13) \) To find the gradient of the tangent to the curve at a specific point, we'll first find the derivative of the function, which represents the gradient function. Given: \[ y = 4x^2 - 2x + 1 \] **Step 1: Find the derivative \( \frac{dy}{dx} \).** \[ \frac{dy}{dx} = \frac{d}{dx}(4x^2) - \frac{d}{dx}(2x) + \frac{d}{dx}(1) = 8x - 2 + 0 = 8x - 2 \] **Step 2: Evaluate the derivative at \( x = 2 \).** \[ \left.\frac{dy}{dx}\right|_{x=2} = 8(2) - 2 = 16 - 2 = 14 \] **Conclusion:** The gradient of the tangent to the curve at the point \( (2, 13) \) is **14**. --- ### 2. Determining the Values of \( a \) and \( b \) for the Curve \( y = ax^2 - \frac{b}{x} \) Given the curve: \[ y = ax^2 - \frac{b}{x} \] We know the gradients at specific points: - Gradient is **3** at \( x = 1 \). - Gradient is **-2** at \( x = \frac{1}{2} \). **Step 1: Find the derivative \( \frac{dy}{dx} \).** \[ \frac{dy}{dx} = 2ax + \frac{b}{x^2} \] **Step 2: Set up equations based on the given gradients.** 1. At \( x = 1 \), \( \frac{dy}{dx} = 3 \): \[ 2a(1) + \frac{b}{1^2} = 3 \quad \Rightarrow \quad 2a + b = 3 \quad \text{(Equation 1)} \] 2. At \( x = \frac{1}{2} \), \( \frac{dy}{dx} = -2 \): \[ 2a\left(\frac{1}{2}\right) + \frac{b}{\left(\frac{1}{2}\right)^2} = -2 \quad \Rightarrow \quad a + 4b = -2 \quad \text{(Equation 2)} \] **Step 3: Solve the system of equations.** From **Equation 1**: \[ 2a + b = 3 \quad \Rightarrow \quad a = \frac{3 - b}{2} \] Substitute \( a \) from Equation 1 into **Equation 2**: \[ \frac{3 - b}{2} + 4b = -2 \] Multiply both sides by 2 to eliminate the fraction: \[ 3 - b + 8b = -4 \quad \Rightarrow \quad 3 + 7b = -4 \] \[ 7b = -7 \quad \Rightarrow \quad b = -1 \] Now, substitute \( b = -1 \) back into Equation 1 to find \( a \): \[ 2a + (-1) = 3 \quad \Rightarrow \quad 2a = 4 \quad \Rightarrow \quad a = 2 \] **Conclusion:** The values are: - \( a = 2 \) - \( b = -1 \) --- ### Summary 1. **Gradient at \( (2, 13) \):** \( \frac{dy}{dx} = 8x - 2 \). At \( x = 2 \), the gradient is **14**. 2. **Values of \( a \) and \( b \):** \( a = 2 \) and \( b = -1 \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To start, we need to calculate the gradient of the tangent to the curve \( y=4x^{2}-2x+1 \) at the point \( (2,13) \). We already have the derivative \( \frac{dy}{dx} = 8x - 2 \). By substituting \( x = 2 \) into the derivative: \[ \frac{dy}{dx} \Big|_{x=2} = 8(2) - 2 = 16 - 2 = 14 \] So, the gradient of the tangent at the point \( (2, 13) \) is 14. Next, for the curve \( y = ax^{2} - \frac{b}{x} \), we need to find the values of \( a \) and \( b \) given that the gradients are 3 at \( x=1 \) and -2 at \( x=\frac{1}{2} \). First, we find the derivative of the function: \[ \frac{dy}{dx} = 2ax + \frac{b}{x^{2}} \] Setting \( x = 1 \): \[ 2a(1) + \frac{b}{(1)^{2}} = 3 \quad \Rightarrow \quad 2a + b = 3 \quad \text{(1)} \] Setting \( x = \frac{1}{2} \): \[ 2a\left(\frac{1}{2}\right) + \frac{b}{\left(\frac{1}{2}\right)^{2}} = -2 \quad \Rightarrow \quad a + 4b = -2 \quad \text{(2)} \] Now we solve these two equations (1) and (2) simultaneously. From equation (1): \[ b = 3 - 2a \] Substituting \( b \) into equation (2): \[ a + 4(3 - 2a) = -2 \] Expanding and simplifying: \[ a + 12 - 8a = -2 \quad \Rightarrow \quad -7a = -14 \quad \Rightarrow \quad a = 2 \] Substituting back to find \( b \): \[ b = 3 - 2(2) = 3 - 4 = -1 \] Thus, the values of \( a \) and \( b \) are \( a = 2 \) and \( b = -1 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy